A review on potential of green solvents in hydrothermal liquefaction (HTL) of lignin - Chung Loong, Yiin; Elatta, Odita; Serene Sow Mun, Lock; Kin Wai, Cheah; Yi, Herng Chan; Mee, Kee Wong; Bridgid Lai Fui, Chin; Armando T., Quitain; Soh, Kheang Loh; Suzana, Yusup (Elsevier, 2022)
One of the greatest challenges in biorefinery is to reduce biomass’ recalcitrance and enable valorization of lignin into higher value compounds. Likewise, green solvents and hydrothermal liquefaction (HTL) with feasible economic viability, functionality, and environmental sustainability have been widely introduced in extraction and conversion of lignin. This review starts with the underscore of disadvantages and limitations of conventional pretreatment approaches and role of green solvents in lignin extraction. Subsequently, the effect of process parameters along with the reaction mechanisms and kinetics on conversion of lignin through HTL were comprehensively reviewed. The limitations of green solvents in extraction and HTL of lignin from biomass were discussed based on the current advancements of the field and future research scopes were also proposed. More details info on HTL of biomass derived lignin which avoid the energy-intensive drying procedures are crucial for the accelerated development and deployment of the advanced lignin biorefinery.